PS 13-05 PENTRAXIN-3 REGULATES THE INFLAMMATORY ACTIVITY OF MACROPHAGES. (September 2016) - Shiraki, Aya; Kotooka, Norihiko; Komoda, Hiroshi; Hirase, Tetsuaki; Oyama, Jun-ichi; Tanaka, Atsushi; Node, Koichi
Abstract : Objective: Pentraxin-3 (PTX3) reportedly has protective roles in atherosclerosis and myocardial infarction, and is a useful biomarker of vascular inflammation. However, the detailed functions of PTX3 in inflammation are yet to be elucidated. This study aims to investigate the function of PTX3 in macrophages. Design and Method: PMA-treated THP-1 cell line (THP-1 macrophage) and monocyte-derived human primary macrophages were treated with recombinant PTX3. Cytokine and chemokine levels in the THP-1 culture medium were measured as well as monocyte chemoattractant protein (MCP-1) concentrations in the Raw 264.7 cell culture medium. PTX3-silenced apoptotic macrophages (THP-1 cell line) were generated to investigate the roles of PTX3 in phagocytosis. Results: In the presence of PTX3, macrophage interleukin-1b (IL-1b), tumor necrosis factor-alpha (TNF-a) and MCP-1 levels were reduced significantly (−39%, P = 0.007; -21%, P = 0.008; and-67%, P = 0.0003, respectively), whilst the activated transforming growth factor-b (TGF-b) was detected in the THP-1 macrophages (P = 0.0004). Additionally, PTX3 induced Akt phosphorylation and reduced the nuclear factor-kappa B (NF-κB) activation by 35% (P = 0.002), which was induced by TNF-a in THP-1 macrophages. Furthermore, the silencing of PTX3 in apoptotic cells resulted in the increased macrophage binding, elevated expression rate of HLA-DR (+30%, P = 0.015) and CD86 (+204%, P = 0.004) positive cells, and induction of IL-1b (+36%, P = 0.024) production. Conversely, adding recombinant PTX3 to macrophages reduced CD86 and HLA-DR expression in a dose-dependent manner. Conclusions: We identified PTX3 as a novel regulator of macrophage activity, which suggests that PTX3 acts to resolve inflammation.